Influence of Calsination Temperature on Zeolite Synthesis from Non-Hazardous Wastes and Its Application as an Adsorbent of Mn Metal Ion - Septiani, Upita; Syukri; Mia Yeliandri; Safni; Zilfa (Departemen Kimia Universitas Andalas, 2025)
In this research, zeolite material was synthesized by hydrothermal method using non- hazardou waste of fly ash as the raw material at low crystallization temperatures of 70oC with seawater as solvent. The effect of calsination temperature on synthesis of zeolite was studied, and the ability of synthesized zeolite to adsorb Mn metal ion in aqueous solution was also investigated. The synthesized zeolite was characterized by Fourier Transform Infra-Red (FT-IR), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM-EDS), and Surface Area Analyzer (SAA). Based on the results of XRD, the type of zeolites produced from the synthesized zeolite are zeolite X and sodalite. The synthesized zeolite was then tested for the adsorption of Mn metal ion, using atomic absorption spectrophotometer (AAS) and it was found that the zeolite material synthesized calcined 550oC had the highest adsorption capacity compared to other synthesized zeolite materials, where the maximum adsorption was 192,31 mg/g.